MENGGUGAT OTENTISITAS EPISTEMOLOGI HUKUM ISLAM : (Studi Kritik Sanad Common Link G.H.A Juynboll) - Khoiri, M. Alim (Universum, 2023)
This paper examines one of the branches in the discipline of hadith which is related to the criticism of sanad. This type of research is library research, that is, researching data related to the discussion by examining references related to the main theme. The focus of this article is to discuss the common link theory used as a weapon by G.H.A Juynboll in criticizing one of the epistemologies in Islamic law, namely hadith. In his conclusion, Juynboll emphasized that so far the authenticity of the hadiths often used by Muslims is doubtful because they are considered to have been 'falsification' by narrators with common link status.